Brain-computer interface (BCI) game for mindfulness training - Goh, Shi Yong (2019)
Mindfulness training has been known to provide individuals with a sense of overall well-being. This project aims to explore innovative ways to integrate EEG headbands to help people train mindfulness with non-invasive feedbacks. Experiments were designed and conducted to collect EEG data to build a classification model. The classification model was then used in the prediction of the mindfulness state of the players. The feedback generated helps to train the player’s mindfulness level by informing them when they are not being mindful and encourages them when they are on the right path. It helps to improve their mental and physical health. In this stressful world of constant brain power usage, mindfulness training is the perfect solution to help an individual relax and take care of their most important asset, the brain.